Role of Lectin in the Response of Aedes aegypti Against Bt Toxin - Alam, Intikhab; Batool, Khadija; Idris, Aisha Lawan; Tan, Weilong; Guan, Xiong; Zhang, Lingling (Frontiers in Immunology, 2022)
Aedes aegypti is one of the most dangerous mosquitoes globally and plays a crucial role as a vector for human diseases, such as yellow fever, dengue, Zika virus disease, and chikungunya. Currently, a major challenge worldwide is the insufficient availability of antiviral drugs and vaccines for arboviruses. Toxins produced by Bacillus thuringiensis var israelensis (Bti) are used as biological agents for mosquito control. Endotoxins, including Cry4Aa, Cry4Ba, Cry10Aa, Cry11Aa, and Cyt1Aa, are toxic to mosquitoes. The use of Cry toxins to kill insects mainly depends on the interaction between Cry toxins and important toxin receptors, such as alkaline phosphatase (ALP), aminopeptidase (APN), cadherin (CAD), and ATP-binding cassette (ABC) transporters. The carbohydrate recognition domains (CRDs) of lectins and Cry toxin domains II and III adopt similar structural folds, suggesting that midgut proteins, such as C-type lectins (CTLs), may interfere with interactions between Cry toxins and toxin receptors by binding to both Cry toxins and receptors to alter Cry toxicity. In the present review, we summarize the role of C-type lectins in Ae. aegypti mosquitoes and the mechanism underlying the alteration of Cry toxin activity by CTLs. Furthermore, we outline future research directions on elucidating the Bti resistance mechanism. This study provides a basis for understanding Bti resistance, which can be used to develop novel insecticides.